ANALISIS PENGEMBANGAN DESA PERHUTANAN SOSIAL BERBASIS KOMODITI KOPI MELALUI SUSTAINABLE LIVELIHOOD APPROACH: STUDI KASUS DESA KEKUYANG KECAMATAN KETOL KABUPATEN ACEH TENGAH - Aulia, Muhammad Reza; Pramulya, Rahmat; Fachruddin, Fachruddin; Ariska, Nana; Sulindawati, Rishi; Mauliza, Rahma (Jurnal Pertanian Agros, 2025)
The Sustainable Livelihood Approach (SLA) is very relevant in managing coffee commodities in Central Aceh through the Social Forestry program that allows communities to manage forests sustainably. This study used in-depth interviews, focus group discussions (FGDs), and field observations to understand the factors that influence the sustainability of community livelihoods. SLA assesses five main assets, namely natural, human, physical, financial, and social. Although human and physical assets have potential, there is an urgent need to strengthen access to social and financial assets. Limited education, skills, and less solid social networks can hinder community economic development. Although infrastructure and natural resources are supportive, dependence on financial access and cooperation between community members is still a major challenge. To improve community welfare and coffee sustainability, there needs to be increased training and more practical counseling, as well as access to capital through microfinance institutions. Building stronger social networks, with collaboration from external parties such as government and non-governmental organizations, is important to strengthen community solidarity. These steps are expected to increase the economic and social resilience of the community while maintaining environmental sustainability.